Peranan Ombudsman Republik Indonesia Perwakilan Sumatera Utara Dalam Pengawasan Pelayanan Dinas Kependudukan dan Catatan Sipil Kota Medan - Putri Ananda Sari; Abdul Kadir; Beby Mashito Batu Bara (Universitas Medan Area, 2019)
This study aims to determine the role of the Ombudsman of the Republic of Indonesia in North Sumatra Representative in the Supervision of Population and Civil Registry Service in Medan City. This study uses a qualitative approach with descriptive methods describing information about the data obtained from the field in the form of written and oral data from the parties studied. Data is collected based on interviews and documentation. The results of this study indicate that the role of the Ombudsman of the Republic of Indonesia in North Sumatra was carried out in the form of external supervision. External supervision is supervision carried out by the Ombudsman of the Republic of Indonesia Representative of North Sumatra to the Medan Population and Civil Registry Service. Actions taken in the supervision process are incoming reports, follow-up of the first report and follow-up of the report. Based on the research that has been carried out, it has been concluded that the role of the Ombudsman of the Republic of Indonesia in the North Sumatra Representative in supervising the service provider of the Population and Civil Registry services is carried out in the form of external supervision. In supervising the handling of public reports of alleged poor service in the area of population administration, it has been effective, with several efforts to handle reports such as: (1) Clarification; (2) Investigation; (3) Recommendations; (4) Monitoring.